Peran Inkubator Bisnis dalam Penguatan Sistem Operasional pada IKM “SEKOTAK DARI DAPUR BU’SARHAN” di Kota Palu - Syah, Ardhi Arilla; Asngadi, Asngadi; Dwiwijaya, Kadek Agus; Kaseng, Saharuddin (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
In the rapidly evolving era of digitalization, digital business incubators have emerged as programs or institutions aiding the development and growth of startups or small businesses focused on digital technology. As part of these dynamic changes, Palu City has introduced a digital business incubator to facilitate the development of local businesses. While this program aims to enhance capabilities, it also faces numerous challenges that may arise during its implementation. Therefore, monitoring is crucial to assess the effectiveness of the mentoring provided, ensuring that the business support offered by the incubator improves business prospects for micro, small, and medium enterprises (MSMEs). Based on these considerations, the research aims to examine the role of Palu City's Business Incubator in strengthening operations at IKM Sekotak Dari Dapur Bu’Sarhan. This study adopts a quantitative approach utilizing SWOT Analysis and the Business Model Canvas (BMC) method to evaluate the outcomes of the incubator's activities for IKM Sekotak Bu’Sarhan. The findings indicate that Palu City's Business Incubator has effectively supported IKM Sekotak Dari Dapur Bu’Sarhan through initiatives such as product legality, digital marketing, branding, quality management, financial management, and awards during the incubation and intensive mentoring period, significantly benefiting the operational management of these businesses.